2013
DOI: 10.1111/cxo.12051
|View full text |Cite
|
Sign up to set email alerts
|

Refractive surgery for keratoconus

Abstract: Traditionally, keratoconus has been managed with glasses when mild, contact lenses when moderate and keratoplasty when severe. When cornea-based refractive surgery was first developed it appeared to be a useful option for keratoconus until reports of post-operative progressive ectasia emerged and thus keratoconus was considered a contraindication to refractive surgery. However, improvements in older techniques and the development of new techniques mean that there are now several viable options to avoid keratop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 106 publications
(194 reference statements)
1
11
0
1
Order By: Relevance
“…15,22 Evidence has shown that corneas from patients with KC contain reduced amounts of total collagen proteins and that defective cross-linking of collagen molecules has been implicated in KC pathogenesis. 23 In our study, we found that COL4A4 rs2229813 AA genotype and A allele act as risk factors for developing KC in our population. The COL4A4 rs2229813 AA genotype was observed more frequent in patients than in the controls (21% vs. 14%); in addition, the COL4A4 rs2229813 A allele was found to be more prevalent in patients with KC compared with healthy subjects (44% vs. 34%).…”
Section: Discussionsupporting
confidence: 48%
“…15,22 Evidence has shown that corneas from patients with KC contain reduced amounts of total collagen proteins and that defective cross-linking of collagen molecules has been implicated in KC pathogenesis. 23 In our study, we found that COL4A4 rs2229813 AA genotype and A allele act as risk factors for developing KC in our population. The COL4A4 rs2229813 AA genotype was observed more frequent in patients than in the controls (21% vs. 14%); in addition, the COL4A4 rs2229813 A allele was found to be more prevalent in patients with KC compared with healthy subjects (44% vs. 34%).…”
Section: Discussionsupporting
confidence: 48%
“…Results need to be interpreted with caution, because not all included cases seem to be representative of keratoconus. It is suggested that topography-guided ablation may be the best choice for such cases 128. Topography-guided conductive keratoplasty has been proposed as a means of reshaping the cornea in advanced cases of keratoconus 129.…”
Section: Managementmentioning
confidence: 99%
“…This technique has the advantage to preserve the integrity of the post-transplant graft, prevent tissue ablation, having no risk of postoperative turbidity, and correcting high degrees of spherical and astigmatic refraction, and they are stable, safe, and effective and can correct elevated refractive errors [24][25][26][27].…”
Section: Phakic Anterior Iols For Keratoconusmentioning
confidence: 99%